Survey of the improvement of fish fermentation for lanhouin production in Benin - DOSSOU-YOVO, PIERRE; JOSSE, Roger Gérard; BOKOSSA YAOU, Innocent Padonou; Palaguina, Iraïda (My University, 2011)
The objective of this study was to control ‘maturation’ process of fish during the fermentation, by using bio-organisms that can give the expected improvement. Starter culture of Lactobacillus plantarum was used as bio-organism on species of fish such as Pseudotolithus senegalensis and Scomberomorus tritor. The inoculum was serially diluted (10–1 to 10–5) in sterile Ringer solution. The result of this improved method showed significantly a product with a mild odour compared to odour from lanhouin traditionally obtained by chance fermentation.
Keywords: Fermentation; fish; Lactobacillus plantarum; maturation; lanhouin.